Regional Security in Central Asia After the Return of the Taliban to Power: Challenges and Threats, Scenarios - Ainur Dzhorobekova; Evgeny Troitskiy; Sergey Yun; Alexey Timoshenko (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2023)
Introduction. The article focuses on reconstructing the major parameters of the complex of challenges and threats to post-Soviet Central Asia regional security that has emerged in the wake of or in direct connection with the radical change of the situation in Afghanistan after August 2021. These challenges and threats have developed across several functional and territorial dimensions and require a comprehensive analysis followed by the building of scenarios for their evolution. Methods and materials. The research relies on the regional security complex theory developed by Barry Buzan and Ole Waever. The methodological toolkit includes external indirect observation, political descriptive and historical genetic methods, scenario building. The research materials include official statements, news briefs, expert opinions, periodicals, academic papers. Analysis. The authors have analyzed the geostrategic, regional-strategic, regional-economic, and regional-societal dimensions of the challenges and threats to Central Asian regional security generated by the changes in Afghanistan and have built scenarios of their evolution. The major geostrategic challenge is the exacerbation of U.S. – Chinese contradictions centered on the influence of the Taliban factions. The key regional-strategic threat is the risk of the Afghan conflict spilling over into Tajikistan or Turkmenistan. The regional-economic challenges include the risks of blocking trans-Afghan transport, pipeline, and electricity transmission projects. The regional-societal risks consist of the dissemination of radical Islamist ideologies from Afghanistan throughout Central Asia. The two basic scenarios of the regional security evolution are inertia or a resumption of a full-scale civil war in Afghanistan. Results. The authors have worked out sets of recommendations for regional policymakers and the intergovernmental bodies whose functions include maintaining security and stability in Central Asia. Authors’ contribution. A.E. Dzhorobekova has developed the general concept of the article and organized the research. E.F. Troitskiy has focused on the analysis of threats and challenges to regional security. S.M. Yun has developed scenarios for regional security situations. A.G. Timoshenko has formulated the relevant recommendations.